2018
DOI: 10.1002/adfm.201805698
|View full text |Cite
|
Sign up to set email alerts
|

An Unusual Red Carbon Nitride to Boost the Photoelectrochemical Performance of Wide Bandgap Photoanodes

Abstract: Tuning the bandgap of a semiconductor to achieve strong band-to-band visible light absorption is highly desirable but challenging for photocatalysis. This work presents a facile molten-salt-assisted route to prepare red-colored polymerized carbon nitride (RPCN) nanosheets with a remarkable redshifted absorption and narrowed bandgap of 1.9 eV. Both experimental findings and theoretical calculations reveal that alkali heteroatoms are effective to tune the surface and electronic structures of carbon nitride, resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
64
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 113 publications
(67 citation statements)
references
References 70 publications
3
64
0
Order By: Relevance
“…C 3 N 4 sensitized TiO 2 nanotube showed 1.5 mA/cm 2 [28]. Yang et al reported red C 3 N 4 , which exhibited 2.2 mA/cm 2 in a higher voltage range, whereas in the lower voltage region it only showed 0.5 mA/cm 2 [40]. The current work demonstrates the role of thiourea on the photoelectrochemical performance and it is noteworthy that the photoelectrode TiO 2 /C 3 N 4 -CMT achieved 2.74 mA/cm 2 , which is highest photocurrent density reported for C 3 N 4 sensitized TiO 2 till date.…”
Section: Discussionmentioning
confidence: 99%
“…C 3 N 4 sensitized TiO 2 nanotube showed 1.5 mA/cm 2 [28]. Yang et al reported red C 3 N 4 , which exhibited 2.2 mA/cm 2 in a higher voltage range, whereas in the lower voltage region it only showed 0.5 mA/cm 2 [40]. The current work demonstrates the role of thiourea on the photoelectrochemical performance and it is noteworthy that the photoelectrode TiO 2 /C 3 N 4 -CMT achieved 2.74 mA/cm 2 , which is highest photocurrent density reported for C 3 N 4 sensitized TiO 2 till date.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with solvothermal method, MSM can provide a higher temperature treatment process and liquid reaction environment, which make the combination of doped elements and matrix more stable. [ 18,81,82 ] At the same time, the liquid environment provided by molten salt makes the element distribution more uniform. In addition, the post‐treatment after the end of the reaction is simpler, and the excess salt can be removed by solvent cleaning.…”
Section: Advantages Of Msm For Photocatalyst Synthesismentioning
confidence: 99%
“…[ 1–4 ] Currently, nonprecious metal‐free photocatalyst with remarkable activity is widely reckoned as an appealing one in photocatalytic energy conversion due to the sustained availability and economic adaptability. [ 5–8 ] Among them, g‐C 3 N 4 is characterized by its many excellent properties, such as thermodynamically suitability (≈600 °C), [ 9 ] moderate bandgap (≈2.7 eV), [ 10,11 ] van der Waals effect, [ 12–14 ] and high polymeric flexibility. [ 15,16 ] Moreover, owing to the common availability by using earth‐abundant carbon/nitrogen‐contained precursors (such as melamine, urea, cyanamide, and thiourea) through a thermal condensation process, g‐C 3 N 4 has been introduced as a significant metal‐free material in various photocatalytic applications.…”
Section: Introductionmentioning
confidence: 99%